Knowledge Utilisation in AgriFood SMEs: Effects of Organisational and Informational Factors - Yawson, David Eshun (Archives of Business Research, 2020)
Given the critical role of information and marketing in SME management it is surprising that little attention has been paid to the salient factors that motivate or inhibits consumer information used by agrifood SMEs. A model of organisational and informational factors affecting knowledge utilisation in Agri-food SMEs is presented and empirically tested through partial least squares analysis via SmartPLS. The results of the empirical testing of the conceptual model provide evidence to indicate that functional and technical qualities, provider-user interaction and usefulness in the market environment are determinants of knowledge utilisation. The findings of this study have implications for agri-food SME management in the UK regarding their growth and competitiveness in the medium and long term.